Framework For Resolving Environmental Damages in Niger Delta Through Deterrence Measures - Ya’u, Abba; Saad, Natrah; Mas’ud, Abdulsalam (European Publisher, 2019)
Documented evidences show that there are about 13 million tons of hydrocarbons spillages in the Niger Delta region, which causes substantive land and coastal contamination. As a result, more than 2000 land were contaminated with oil that posit serious economic problem for the communities. When an oil spill occurs on the land, fires often break out, killing vegetation and creating a crust over the land, making remediation or revegetation difficult. The objective of this paper is to propose the use of economic deterrence model as a panacea for the restoration/remediation of Niger Delta. A thorough search of the following databases; United Nations (UN) database, World Bank database, International Monetary Fund (IMF) database, Transparency International database, Human Rights Watch Reports, African Union (AU) Reports, Scopus database, Web of Science, Emerald, Google Scholar, among others were conducted to come up with the relevant and related literature on the subject matter. Economic deterrence approach nexus with effective enforcement of environmental taxation could be one of the best restoration approaches to the endemic social, political and economic problem of Niger Delta, hence, a framework using this approach is proposed in this study. Validation of this framework can serve as a policy tools available to the government, to restore contaminated land and other environmental challenges cause by oil and gas company’s operation. Finally, the study design to guide policymakers, especially in developing countries to explore the model so as to achieve the desired environmental policy.